2020
DOI: 10.1021/acs.molpharmaceut.0c00831
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Replacement Therapy for Mucopolysaccharidosis IIID using Recombinant Human α-N-Acetylglucosamine-6-Sulfatase in Neonatal Mice

Abstract: There is currently no cure or effective treatment available for mucopolysaccharidosis type IIID (MPS IIID, Sanfilippo syndrome type D), a lysosomal storage disorder (LSD) caused by the deficiency of α-N-acetylglucosamine-6-sulfatase (GNS). The clinical symptoms of MPS IIID, like other subtypes of Sanfilippo syndrome, are largely localized to the central nervous system (CNS), and any treatments aiming to ameliorate or reverse the catastrophic and fatal neurologic decline caused by this disease need to be delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 98 publications
1
8
0
Order By: Relevance
“…In addition, the increases in LDLR, APOB and NAGLU were also observed from our previous proteomic data (Figure S1B) [16]. To validate our proteomic data, we used enzymatic activity assays to measure the active enzyme levels of NAGLU and HEXB [23,24]. Our results showed UPCDC-30245 treated samples have significant increase of HEXB and NAGLU enzymatic activities (Figure 2E), and we demonstrated that UPCDC-30245 did not affect their activities when added directly to cell lysate (Figure 2E), which is consistent with the increased protein levels in our proteomic data.…”
Section: Proteomics Reveals Impairment Of Endo-lysosomal Pathways In ...supporting
confidence: 76%
See 1 more Smart Citation
“…In addition, the increases in LDLR, APOB and NAGLU were also observed from our previous proteomic data (Figure S1B) [16]. To validate our proteomic data, we used enzymatic activity assays to measure the active enzyme levels of NAGLU and HEXB [23,24]. Our results showed UPCDC-30245 treated samples have significant increase of HEXB and NAGLU enzymatic activities (Figure 2E), and we demonstrated that UPCDC-30245 did not affect their activities when added directly to cell lysate (Figure 2E), which is consistent with the increased protein levels in our proteomic data.…”
Section: Proteomics Reveals Impairment Of Endo-lysosomal Pathways In ...supporting
confidence: 76%
“…Therefore, the reduction of early endosomes is a cellular effect potentially unique to UPCDC-30245. The upregulation of LAMP1, lysosomal enzymes (HEXB and NAGLU) as well as autophagy has been found in multiple lysosome storage diseases (LSDs) [23,24,49]. LSDs are caused by the insufficient degradation of (GAGs) due the deficiency of certain lysosome enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Both rAAV‐mediated gene and enzyme replacement therapies have been applied to TPP1 deficiency (Katz et al, 2015). Intracranial delivery of rAAV has shown an exponential increase in TPP1 enzyme activity, while enzyme replacement therapy (ERT) has shown an improvement in the symptomatology and neuropathology of the disease, both in vitro using human fibroblast and in vivo using murine models and non‐human primates (Wang et al, 2021).…”
Section: Murine Modelsmentioning
confidence: 99%
“…The human full-length NAGLU cDNA (amino acid 1-743) in pEE12.4/NAGLU-IGFII with a C-terminal myc tag (25) was subcloned into pOptiVEC™-TOPO® shuttle vector (Invitrogen), bearing a gene coding for dihydrofolate reductase (DHFR). A human full-length GNS cDNA (amino acid 1-552) followed by a myc tag was subcloned into pOptiVEC™-TOPO® vector as described (26). To construct rhGNS with an artificial signal peptide, the signal peptides followed by a XhoI site were fused at the 5' primer of the GNS coding sequence.…”
Section: Plasmid Dna Constructionmentioning
confidence: 99%
“…NAGLU or GNS activity was measured in triplicate by detecting the amount of 4-methylumbelliferon (4-MU) to be liberated from the respective fluorogenic substrate for both GNS and NAGLU (25,26).…”
Section: Enzymatic Activity Assays For Rhnaglu and Rhgnsmentioning
confidence: 99%